Resposta imune humoral em bovinos da raça nelore vacinados contra a raiva e suplementados com crômio orgânico - Giometti, José [UNESP] (2004)
With the objective of to evaluate the effect of the addition of orgainc chromium in the humoral immune response against rabies, five Neloreþs bovine breed groups with 15 animals each, were supplementeds with chromium yeast being the group GC (control), GV (vaccinated and without chromium), GV+8,5 (vaccinated + 8,5 ppm of chromium), GV+17 (vaccinated + 17 ppm of chromium) and GV+34 (vaccinated +34 ppm of chromium). Serum samples of this animals were analyseds with serum neutralization test (SN) in albines mices in the days 30,60 and 90 pos -vaccination. Simultaneously, serum concentrations of the chromium were determinated for analysis with spectrophotometer of atomic absorption in graphite oven and analysis of the cortisol was achieved through of the radioimmunoassay.These results allows to conclude that the animals of the group GV+34 have persistence of the protector's antibody titulation anti rabies until 90 days pos- vaccination. This response does not dependt of the cortisol levels, since the chromium donþt show to be effective to decrease its levels.